2009
DOI: 10.1038/sj.bjc.6605502
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-21 can efficiently restore impaired antibody-dependent cell-mediated cytotoxicity in patients with oesophageal squamous cell carcinoma

Abstract: BACKGROUND: We previously reported that Trastuzumab-and Cetuximab-mediated antibody-dependent cell-mediated cytotoxicity (ADCC) in cancer patients was impaired in comparison with that in healthy donors because of NK-cell dysfunction. In this study, we evaluated whether IL-21 could improve the impairment of ADCC in patients with oesophageal squamous cell carcinoma (ESCC), as IL-21 was reported to have the ability to activate NK cells. METHODS: We examined Trastuzumab-and Cetuximab-mediated ADCC of peripheral bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…In our in vitro system, pre-treating the PBMC effector cells overnight with IL2 did not increase the avelumab-induced ADCC activity (Supplementary Table S1). It has been shown that IL21 can enhance the in vitro ADCC activity of both trastuzumab and cetuximab (45). Studies are now emerging that IL15 can greatly enhance NK cells in both experimental systems and clinical studies (46, 47).…”
Section: Discussionmentioning
confidence: 99%
“…In our in vitro system, pre-treating the PBMC effector cells overnight with IL2 did not increase the avelumab-induced ADCC activity (Supplementary Table S1). It has been shown that IL21 can enhance the in vitro ADCC activity of both trastuzumab and cetuximab (45). Studies are now emerging that IL15 can greatly enhance NK cells in both experimental systems and clinical studies (46, 47).…”
Section: Discussionmentioning
confidence: 99%
“…One of the possibilities is the low proportion of CD3 -CD56 ? (NK cells) infiltrating CRC tumors [20] and the low functional capacity of these cells observed in cancer patients [21][22][23]. Therefore, if we could enhance the activity of NK cells, the efficacy of treatment with Cetuximab could be increased.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms include a shift from a T helper 1 (T H 1)Ytype to a T H 2-type cytokine response, 1 dysfunction of cytotoxic CD8 + T cells and natural killer (NK) cells, induction of T regulatory (Treg) cells, and so on. 2 Among human CD4 + T cells, besides the traditional T H 1 and T H 2 helper cell subsets, 2 novel subsets have been identified, namely, Treg cells and T H 17 cells. T regulatory cells have been implicated in the progression of various tumors through obstruction of the development of effective antitumor immunity, 3 as Treg cells are found higher in the peripheral blood of cancer patients.…”
mentioning
confidence: 99%
“…2,8 Interleukin 21 has been shown to be an important autocrine factor of T H 17 cells. 9 Interleukin 12 is known to be an NK cell stimulatory factor and a cytotoxic lymphocyte maturation factor 10 and inhibits Treg cell proliferation and activities.…”
mentioning
confidence: 99%